2012
DOI: 10.1007/s10549-012-2356-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic evaluation of the B cell/IL-8 metagene in different intrinsic breast cancer subtypes

Abstract: We recently reported that a ratio of high B cell and low IL-8 metagene expression identified 32 % of triple negative breast cancers (TNBC) with good prognosis and was the only significant predictor in multivariate analysis including routine clinicopathological variables. However, the clinical relevance of this signature in other breast cancer subtypes remains unclear. We compiled Affymetrix gene expression datasets from 4,467 primary breast cancer samples and excluded 329 triple negative samples which were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…We compiled Affymetrix gene expression profiles of a total of 4467 breast cancer patients from 40 publicly available datasets as previously reported (Hanker et al., 2013) (see Methods section and Supplementary Table S1 and Figure 1). The clinical characteristics of all 4467 samples are given in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…We compiled Affymetrix gene expression profiles of a total of 4467 breast cancer patients from 40 publicly available datasets as previously reported (Hanker et al., 2013) (see Methods section and Supplementary Table S1 and Figure 1). The clinical characteristics of all 4467 samples are given in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, a high B-cells and low IL-8 metagenes have been associated with good prognosis in this population, suggesting that IL-8 suppression may be a therapeutic approach 74. In another study, a group of 14 genes linked to immune/inflammatory cytokine regulation identified TNBC patients with a good outcome in the absence of aggressive adjuvant therapy 75.…”
Section: Gene Signatures In Er-negative Breast Cancermentioning
confidence: 94%
“…We compiled Affymetrix gene expression data (U133A or U133Plus2.0 arrays) of 4467 breast cancer patients from 40 publicly available datasets as previously described [17,33] (Supplementary Table 1). All analyses were performed according to the ''REporting recommendations for tumour MARKer prognostic studies'' (REMARK) [26,34] and the respective guidelines to microarray-based studies for clinical outcomes [12].…”
Section: Patientsmentioning
confidence: 99%